Rural nonfarm enterprises in Tanzania's economic transformation: The role of the youth - Diao, Xinshen; Magalhaes, Eduardo; McMillan, Margaret S. (International Food Policy Research Institute, 2019)
Chapter 8 combine household and firm level analysis for Tanzania to examine what determines the success of rural nonfarm enterprises, including the role of young entrepreneurs.